Effect of Clove Oil Addition on Edible Coating and Film on Bacterial Activity in Skipjack Fish Fillets - Souhoka, Fensia Analda; Kapelle, Imanuel Berly Delvis; Lilipaly, Reggi Austin (Universitas Gadjah Mada, 2024)
Using bioactive compounds in environmentally friendly food packaging can extend the shelf life of food. This study aimed to determine how adding clove oil in manufacturing edible coatings and chitosan films affects bacterial activity in skipjack tuna fillets. Edible coatings and films made from 1% chitosan were prepared by adding clove oil with a concentration of 1; 2; 3; 4; and 5%. The edible solution was applied to the skipjack tuna fillets using two packaging techniques: edible coating by immersing the sample for two minutes and edible film by wrapping the sample. The microbial activity test was carried out using the total plate count (TPC) method a microbiological test to count the number of live cells or colony-forming units in food. The maximum number of bacterial colonies using the TPC test based on SNI 01-2332.3-2006 for fishery products is 1.0x105 colonies/g. The number of bacterial colonies in the edible coating sample was 1.9x103–2.4x104 CFU/g, while the edible film sample was 1.8x104–2.4x105 CFU/g. Adding clove oil affected the TPC value compared to the untreated chitosan edible. Using bioactive compounds in environmentally friendly food packaging can extend the shelf life of food. The number of edible coating colonies on adding 1% clove oil was 5.8x103 CFU/g, lower than edible film 4.1x104 CFU/g and complying with SNI. Applying an edible coating on skipjack tuna fillets with 1-5% clove oil is better than using edible film regarding the TPC value.